Aesthetic experience and emancipation in the cultural philosophical thinking of Raúl Roa García (Islas, 2022)
This article examines the place of the aesthetic experience in the cultural philosophical conceptions of Raúl Roa García, during the period between 1940 and 1958. To do this, an interpretive hermeneutic study of some of his works written and published in the stated period is carried out, since it was his stage of most prolific intellectual reflection. Starting from locating the theoretical developments around the aesthetic experience category, we proceeded to assess how this is conceived in Roa's cultural thought, as well as the nuances it brings to his discourse, his position as an intellectual trained in a Western tradition and illustrated that it intends to overcome through the apprehension of Marxism and the Martian legacy. As a result, it can be affirmed that, for Roa, the aesthetic experience is a way of connecting rational thought with sensibility, while claiming the possibilities of the latter to build knowledge. Moreover, it constitutes a tool to deconstruct the cultural expressions of domination and build politics through dissent: its postulates are based on the possibilities of forming critical subjects in order to democratize access to culture for the most neglected social sectors. In this sense, it is concluded that in Raúl Roa the aesthetic experience is projected on a collective level, as he seeks the achievement of social justice, and on an individual level, as he seeks the emancipation of the individual from the ascension of the spirituality.
Keywords: Cultural philosophy; Culture; Aesthetic; Politics; Cuba